Satisfaction Level of Patients of Nursing Services Provided in a Hospital - Thapa, Nirupa (Journal of Nursing Education of Nepal, 2023)
A descriptive exploratory research design was carried out to identify the satisfaction level of  patients toward nursing service during hospitalization in Western Regional Hospital, Pokhara.  The main objective was to identify the satisfaction level of patients toward nursing services.  A total number of 100 patients were selected by using non- probability purposive sampling  technique. Structured interview schedule and three points Likert scales were used for data  collection. The obtained data were coded and entered in SPSS version 16 programs and analyzed  by using descriptive statistics. The study findings revealed that 38.00 percent of the respondents not satisfied, 39.00 percent of  the respondents partially satisfied and only 23.00 percent of the respondents were satisfied with  mean score of 38.10 ±4.61. The study concluded that the respondents were partially satisfied toward nursing services. There  is need to plan and implement the training programs for nurses to improve their knowledge and  skills of communication and use of emotional support measures for the patients.
Keywords: Satisfaction level of Patients; Nursing service